Rumah Susun ASN Polda Sulawesi Selatan di Kota Makassar - Dewa Ammar; Abd. Aziz Alimuddin; Andas Budy (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
Housing is one of the important components of regional development strategies because it involves various aspects of population and is closely related to economic development and social life. Flats or apartment buildings have now become a popular choice of housing in urban areas due to the increasing population and limited available land. This study employs a data collection method comprising primary and secondary data. Primary data was obtained directly from the research site through observation and interviews, while secondary data was sourced from other materials such as documents, literature, regulations, and relevant online news articles related to the research topic. The South Sulawesi government is striving to improve the welfare and productivity of Polri members through the construction of flats on Jalan Paccerakkang, Kelurahan Biringkanaya, Makassar City. This construction takes into account architectural aspects to create efficient and functional housing. These flats are expected to improve the quality of life of Polri members and civil servants. The synergy between the government and the police is evident in this development, which aims to provide comfortable and adequate housing for its residents. Thus, the planning of the police and civil servant apartment complex in South Sulawesi can serve as a model for other apartment complex developments, with proper consideration of design, construction, and appropriate allocation to enhance community welfare.